Pengaruh Kualitas Pelayanan dan Electronic Word of Mouth Terhadap Keputusan Pembelian di Rayz UMM Hotel Malang - Ika Fadila Ayu Lestari; Joko Samboro; Rizky Kurniawan Murtiyanto (Indo Publishing, 2025)
Economic growth in various parts of the world, including Indonesia, has shown rapid development. One of the most promising sectors is the hospitality industry, supported by Indonesia’s rich cultural heritage and favorable economic conditions. Hotels play an important role in this sector by providing quality service, creating customer satisfaction, and building long-term relationships. Rayz UMM Hotel Malang is one such hotel that has actively maintained communication with its customers through social media, contributing to a positive image and strong customer engagement.This study employed a quantitave approach. Data were obtained through observation and questionnaires. Sampling was conducted using probability method with a purposive sampling technique, involving a total of 100 respondent. The questionnaire result were measured using a likert scale. Data analysis was carried out using multiple linier regression with SPSS 26 for windows. The result of both partial and simultaneous hypothesis testing indicated that service quality and electronic word of mouth have a positive and significant influence on purchasing decisions at Rayz UMM Hotel Malang. The findings show that service quality variabel has a greater contribution compared to electronic word of mouth. Based on the results of the study, it can be concluded that service quality and electronic word of mouth are important factors that contribute to customer satisfaction. Therefore, it is recommended that the hotel improve its services and strengthen customers’ emotional loyalty through personalized services, the provision of rewards or membership programs, and communication strategies that encourage customers to provide positive recommendations.